2009
DOI: 10.1373/clinchem.2009.123778
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Brain Natriuretic Peptide Concentrations Vary with Age and Sex and Appear to Be Modulated by Testosterone

Abstract: Background: Natriuretic peptide concentrations in adults require age- and sex-specific reference intervals for optimal interpretation. Females have higher natriuretic peptide concentrations, and hypotheses suggest that estrogen may be responsible. This study sought to determine the influence of hormone modulation on N-terminal probrain natriuretic peptide (NT-proBNP) by using a pediatric cohort. Children/adolescents typically have rapid hormone changes during puberty, making them an ideal group to study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 20 publications
3
24
0
1
Order By: Relevance
“…The Dallas Heart Study, observed by Chang et al (9), reported no association between estrogen status and NT-proBNP levels, whereas a strong inverse association was found between measures of free testosterone and NT-proBNP in young women (age range, 35-49 yr). Saenger et al (76) reported an inverse association of NT-proBNP with serum testosterone, a direct association with sex hormone-binding globulin, and no significant association with circulating levels of estradiol in a large population of girls and boys (age range, from 2 mo up to 18 yr).…”
Section: The Cross Talk Between Cardiac Natriuretic and Sex Steroid Hmentioning
confidence: 99%
“…The Dallas Heart Study, observed by Chang et al (9), reported no association between estrogen status and NT-proBNP levels, whereas a strong inverse association was found between measures of free testosterone and NT-proBNP in young women (age range, 35-49 yr). Saenger et al (76) reported an inverse association of NT-proBNP with serum testosterone, a direct association with sex hormone-binding globulin, and no significant association with circulating levels of estradiol in a large population of girls and boys (age range, from 2 mo up to 18 yr).…”
Section: The Cross Talk Between Cardiac Natriuretic and Sex Steroid Hmentioning
confidence: 99%
“…On the other hand, a significant and positive association between SHBG and cardiac natriuretic peptide levels (3)(4)(5) may require an alternative interpretation to the one suggested by Lam et al (5), indicating a relevant influence (instead of no effect) of estrogenic status on BNP/NTproBNP levels. Indeed, sex steroid hormones regulate the liver production of SHBG in an opposite way: estrogens show a powerful stimulatory action, whereas androgens have an inhibitory one (8).…”
Section: See Page 618mentioning
confidence: 88%
“…More recently, 3 large population-based studies have indicated that male sex steroid hormones might modulate cardiac endocrine function too (3)(4)(5). These studies demonstrated a significant inverse association between the circulating levels of B-type natriuretic peptide (BNP) or N-terminal fragment of pro-B-type natriuretic peptide (NT-proBNP) and male sex steroid hormones (i.e., total and free testosterone) in both sexes (3)(4)(5), whereas the association with estradiol was found to be weak or not significant at all (3,4).…”
Section: See Page 618mentioning
confidence: 99%
See 2 more Smart Citations